Granular Flow Modeling of Galvanized Steel Scrap Injection into the HIsarna Iron‐Making Reactor. Issue 11 (26th August 2022) - Hosseini, Ashkan; Georgopoulos, Evangelos; Dihman, Vinod; Hage, Johannes; Meijer, Koen; Zeilstra, Christiaan; Offerman, Erik; Yang, Yongxiang
Abstract : Galvanized steel scrap flow and injection into the HIsarna reactor are investigated using discrete element method (DEM). The scrap particle is fed into the reactor through an inclined chute and hits the slag surface where the zinc content is evaporated and solid particles melt. A DEM model is setup and validated using experimental data obtained from the exact plant‐scale chute geometry and scrap particles. Using the DEM model, the effect of chute inclination, injection elevation, injection mode (batch and continuous), batch size, and flowrate on particle distribution and exerted pressure on the slag surface are investigated. It is found that continuous mode of injection is the most suitable method to increase the spread of particles and also to reduce the exerted pressure on the slag surface. Placing dent‐like obstacles at the tip of the chute significantly increases the impact area, especially for batchwise injection, thus reducing force and pressure on the slag surface that minimizes the risk of liquid splash. Larger particle impact area is also beneficial to obtain higher zinc evaporation rate from particle surface and also to minimize the slag surface temperature disturbance. Abstract : The scrap chute inclination affects particles' landing position on the slag surface. Increasing the spread particles over slag surface lowers impact pressure, reduces splashing, increases zinc evaporation, and reduces temperature disturbance of the slag surface. A continuous injection is preferred over a batch injection for mainly lower impact pressure. Using dent‐shaped obstacles at the tip of the chute creates significantly higher particle spread.